2011
DOI: 10.1007/s00271-011-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals

Abstract: Emitter clogging, a phenomenon commonly seen in reclaimed wastewater drip irrigation systems, is a severe obstacle to the wide applications and popularization of the irrigation technology. Some experiments showed that the emitter clogging was tightly related to biofilms formation attached to the irrigation system. In this paper, two types of wastewaters reclaimed respectively by fluidizedbed reactor (FBR) process and biological aerated filter (BAF) process were chosen as the experiment objects and then the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…Their results partially conform to the fi ndings of this study. It was shown that the suspended particles in reclaimed water are fl occulent and porous [39]. The uniformity of distribution of these pores was reported to be increasing with the size of the solids.…”
Section: Particles In Watermentioning
confidence: 99%
“…Their results partially conform to the fi ndings of this study. It was shown that the suspended particles in reclaimed water are fl occulent and porous [39]. The uniformity of distribution of these pores was reported to be increasing with the size of the solids.…”
Section: Particles In Watermentioning
confidence: 99%
“…However, drip irrigation systems show high susceptibility to emitter clogging (Liu & Huang, 2009;Li et al, 2011; when wastewater is applied (Dazhuang et al, 2009;Yan et al, 2009;Batista et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the problems that the drip irrigation system offers is the possibility of clogging of emitters in the field, due to the low flow drippers (0.6 to 3.5 L h -1 ), necessary for the economic viability of the system, which is one of the biggest impediments to applications and popularization of this technology (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic factors can also contribute in the process of clogging in the field like the inlet pressure, the flow and the speed of water circulation within the system (Capra & Scicolone, 2007;Li et al, 2012;Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%